Quality Comparison of Free-of-Charge Global DSMs: ALOS AW3D30, TanDEM-X 12 m, TanDEM-X EDEM, TanDEM-X 90 m, and Sentinel-1 - U. G. Sefercik; K. Jacobsen (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
Digital Surface Model (DSM), with the height of the visible surface, is the most detailed digital 3D cartographic representation of Earth visible surface including all natural and man-made objects with X, Y planimetric coordinates and altitude Z. DSMs are frequently used in many areas such as agriculture, forestry, architecture, archaeology, disaster monitoring, especially in mapping, and this situation brings with it a high demand. In order to meet these demands, many DSM generation techniques have been developed based on the use of remote sensing technologies. Satellite technologies are used in the generation of DSMs of large areas such as provinces, countries, and continents due to the limited availability of airborne technologies. In this context, the global DSM concept, which has the potential to cover the whole world, has emerged with the beginning of the 2000s. Global DSMs have advantages and disadvantages against each other depending on the sensing principle and properties of the images used for their generation. This study aims to compare the qualities of the mostly preferred free global DSMs worldwide, produced with different sensing principles and image properties, with reference model-based visual and statistical analyses. In the analyses, the qualities of the commercial (free for scientific use) TanDEM-X 12 m (TDM12) and the free ALOS World 3D 30 m (AW3D30), TanDEM-X 30 m edited DEM (TDM EDEM) and TanDEM-X 90 m (TDM90) global DSMs were evaluated using a photogrammetric reference DSM with 5 m grid. Sentinel-1 DSM was also generated with 30 m point spacing and included in the investigations due to availability of free scenes worldwide which can be used for the generation of DSMs globally. The results demonstrated that the quality of the evaluated DSMs was TDM12 > TDM EDEM > AW3D30 > Sentinel-1 > TDM90. Generated height error maps which illustrate the pixel-based height differences between evaluated and reference DSMs revealed all the incoherent areas.